Probiotics for treating acute diarrhea in children: an evidence synthesis - Chen, Cheng; Liu, Pei; Xiao, Lang; Cao, Qian; Zhou, Ding'an; Liu, Xingmei; Shen, Min; Jia, Xu; Zhang, Lin (Frontiers in Pediatrics, 2026)
ObjectiveWe aimed to evaluate the efficacy of probiotics against diarrhea in children.BackgroundAcute diarrhea remains the leading cause of childhood morbidity and mortality worldwide and is one of the most common reasons for child visits and hospitalizations.MethodsRandomized clinical trials (RCTs) of probiotics for the treatment of acute diarrhea in children were identified by searching EMBASE, PubMed, the Cochrane Library, and the Clinicaltrials.gov registry with a search deadline of September 29, 2023. Fixed- and random-effects models were employed, using standardized mean differences (SMDs), relative risk ratios (RRs) and 95% confidence intervals (CIs) as outcome indicators. Primary outcomes included the duration of the child's diarrhea and the number of children with diarrhea at the completion of the trial, and secondary outcomes included the length of the child's hospitalization, the frequency of stools on day 2 post-intervention, and the number of recoveries within 3 days of the intervention. We performed this according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement.ResultsThe study included 25 randomized controlled trials involving 9,071 subjects. After the intervention, moderate evidence indicated that, probiotics shortened the duration of diarrhea in children (SMD=−0.44, 95% CI: −0.70∼−0.17), increased the number of children who recovered from diarrhea, reduced the number of children with diarrhea at the completion of the trial (RR = 0.68, 95% CI: 0.54∼0.86), and reduced the number of stools on d 2 (SMD=−0.38, 95% CI: −0.59∼−0.18), but the quality of evidence was very low. However, there was no effect on children's length of hospitalization (SMD=−0.27, 95% CI: −0.63∼0.09) and the number of recoveries within 3 d after the intervention (RR = 1.70, 95% CI: 0.98∼2.97). Among these, probiotics reduced the average duration of diarrhea by approximately 1.21 days. For the primary outcome, subgroup analyses based on individual probiotic strains, Limosilactobacillus reuteri was found to have a significant trend in reducing the duration of diarrhea (SMD=−0.62,95% CI:−0.92∼−0.32), while Lacticaseibacillus rhamnosus was found to have a significant trend in decreasing the number of children with diarrhea at the completion of the trial (RR = 0.52, 95% CI:0.37∼0.74).ConclusionThe results showed that probiotics demonstrated adequate clinical efficacy in shortening the duration of diarrhea, increasing the number of recoveries in children with diarrhea, reducing the number of diarrhea cases, and alleviating diarrhea symptoms.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, PROSPERO CRD42024534039.